Experiencing Verdi : a listener's companion - Sanders, Donald C. (Listener's companion, 2014)
In Experiencing Verdi: A Listener's Companion, Donald Sanders combines biography with simple, concise musical analysis. Summarizing the evolution of Italian opera and the bel canto tradition that prevailed at the beginning of Verdi's career, Sanders takes readers on a leisurely tour of eleven of Verdi's most important operas and of the Manzoni Requiem and concludes with a look at Verdi's influence on later composers like Giacomo Puccini, his place in the modern repertoire,
Keywords: Verdi, Giuseppe, : 1813-1901 : Criticism and interpretation; Verdi, Giuseppe, : 1813-1901 : Operas; Opera : Italy : 19th century